Allocation of Credit Resources and “Borrow to Lend” Activities: Evidence From Chinese-Listed Companies - Zhao, Shangmei; Wang, Huibo; Li, Wei (Frontiers in Psychology, 2022)
Credit distribution is uneven in the domestic financial market since it is relatively easy for listed companies, mainly state-owned enterprises, to obtain banks’ funds. Unbalanced credit distribution has caused some listed companies to participate in “Borrow to Lend” activities. Based on the traditional “financing priority” theory and credit rationing theory, this paper studies the “Borrow to Lend” shadow banking activities of China’s non-financial listed companies based on the 2007–2018 financial statement data of Chinese-listed companies and discusses the micro-level and macro-level related factors behind this activity. The empirical results show that China’s non-financial listed companies, especially the state-owned enterprises, are participating in obvious “Borrow to Lend” activities. The real economy’s rate of return shows a negative relationship with “Borrow to Lend” activities at the level of individual companies and their industries. This article uses the exogenous growth part of M2 growth to measure monetary policy tightness in terms of macro and credit policies. It uses the ratio of state-owned enterprise loans to total corporate loans as an approximate indicator of the credit distribution structure. The empirical results indicate that state-owned enterprises’ “Borrow to Lend” activities have shifted in the same direction as the tightening of monetary policy after the financial crisis. The proportion of state-owned enterprise loans positively correlates with state-owned enterprises’ “Borrow to Lend” activities.